Advantages and Disadvantages of the Teacher’s Use of the Students’ First Language in a Basic English Course at CIEX “Ignacio Manuel Altamirano” - Granados, Anuar; Castillo, María; Huang, Becky (CIEX JOURNAL, 2016)
The study is focused on the analysis of the advantages and disadvantages of using the first language (Spanish) in an English class. The study also explored the contributions of the students’ L1 in the teaching and learning processes. The context was the Centro de Idiomas Extranjeros (CIEX).The participants were an EFL teacher and his five students in a Basic English course. A qualitative research approach was used with the implementation of interview guides to both the teacher and the students as well as a class observation format. It is important to mention that the following paper focuses only on the design of a BA in English letters thesis.